2013
DOI: 10.4236/fns.2013.411140
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Nutritional Value of the Leaves of <i>Moringa oleifera</i> on Poultry

Abstract: In this study, we validated the effect of Moringa oleifera leaves as food supplement on poultry. Proximate neutron activation analysis was used in determining the level of some of the vital nutritional minerals and potential toxic elements in the serum of the birds during the experimental process, including Magnesium, Copper, Vanadium, Chlorine, Aluminum, Manganese, Calcium, Mercury, Cadmium, Arsenic, Sodium and Potassium. Incorporation of Moringa oleifera leaves in maize meal fed to poultry showed profound, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…Thus, it could be inferred that MOL had a significant impact on the weight of broilers via the provision of vital minerals such as Ca and P which might have been insufficient in the normal diet of the control. This result is in agreement with the findings of Donkor, Glover, Addae, and Kubi () who found that a significant increase in serum calcium was observed for broilers fed with formulated MOL and maize meal during the feeding period compared to the control.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it could be inferred that MOL had a significant impact on the weight of broilers via the provision of vital minerals such as Ca and P which might have been insufficient in the normal diet of the control. This result is in agreement with the findings of Donkor, Glover, Addae, and Kubi () who found that a significant increase in serum calcium was observed for broilers fed with formulated MOL and maize meal during the feeding period compared to the control.…”
Section: Discussionsupporting
confidence: 93%
“…Yolk colour is a preferable trait for consumers and MOL has high concentration of xanthophylls (167.1 ± 6.1 lg/g; Pasaporte et al 2014), which is associated with the colouration of body parts. Donkor et al (2013) also reported that incorporation of MOL led to the intensified colouration of combs, beaks and legs in broilers. In agreement with Ebenebe et al (2013), adding MOL had no effect on egg shape index.…”
Section: Discussionmentioning
confidence: 93%
“…An improvement in egg production, yolk colour and feed conversion ratio were observed in Rhode Island Red hens supplemented with MOL (Mohammed et al 2012). The addition of MOL powder to the diets was associated with increased weight in broilers (Donkor et al 2013). In a recent study, Kholif et al (2015) observed an increased feed intake, nutrient digestibility and milk yield in goats fed diets including MOL.…”
Section: Introductionmentioning
confidence: 98%
“…Segundo Nkukwana et al (2014), a inclusão das folhas de Moringa olifera na dieta de aves como promotor de desempenho, apresentaram efeitos benéficos na melhoria da eficiência alimentar na fase de crescimento das aves, sugerindo que futuras pesquisas, contenham níveis maiores do 2,5% de inclusão dietética para determinar digestão e retenção de nutrientes, o que ajudaria a elucidar o efeito dos compostos bioativos nas folhas sobre desempenho. De acordo com o trabalho de Donkor et al (2013), ao avaliarem a utilização das folhas de Moringa olifera na dieta das aves e os potenciais minerais dessa planta. Esses autores observaram que a inclusão das folhas da moringa na dieta das aves aumentou o ganho de peso e outras características gerais dos frangos de corte, como: bico e pernas brilhantes.…”
Section: Perfil Nutricional E Aplicações Na Nutrição De Avesunclassified